Managing cancer patients during the COVID-19 pandemic: an ESMO multidisciplinary expert consensus - Curigliano, Giuseppe; Banerjee, S.; Cervantes, A.; Garassino, M. C.; Garrido, P.; Girard, N.; Haanen, J.; Jordan, Karin; Lordick, F.; Machiels, J. P.; Michielin, O.; Peters, S.; et al. (Annals of oncology, 2020)
We established an international consortium to review and discuss relevant clinical evidence in order to develop expert consensus statements related to cancer management during the severe acute respiratory syndrome coronavirus 2 related disease (COVID-19) pandemic. The steering committee prepared 10 working packages addressing significant clinical questions from diagnosis to surgery. During a virtual consensus meeting of 62 global experts and one patient advocate, led by the European Society for Medical Oncology, statements were discussed, amended and voted upon. When consensus could not be reached, the panel revised statements until a consensus was reached. Overall, the expert panel agreed on 28 consensus statements that can be used to overcome many of the clinical and technical areas of uncertainty ranging from diagnosis to therapeutic planning and treatment during the COVID-19 pandemic.
Gesehen am 11.02.2021